2003
DOI: 10.1002/cncr.11277
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma after breast‐conserving therapy

Abstract: BACKGROUND Angiosarcoma arising in the irradiated breast after breast‐conserving therapy is being reported with increasing frequency. As more women undergo breast‐conserving therapy, the incidence can be expected to increase. Surgeons, medical oncologists, and radiation oncologists will be faced with difficult management decisions for this aggressive disease. METHODS A comprehensive review of all English‐language reports of angiosarcomas after breast‐conserving therapy was performed. Approximately 100 cases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
227
1
14

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(251 citation statements)
references
References 74 publications
9
227
1
14
Order By: Relevance
“…In addition to RT, lymphedema has been implicated as a potential causative factor in the development of angiosarcoma. 32 Lagrange et al reported that most RIS was high grade, as observed in our study, in which 66% were grade 3. 33 Regarding RIS site, the proportion of sarcomas that arose from the maxillary sinus in the current study cohort (18.9%) was consistent with the data reported by Wang et al 17 RIS traditionally has been viewed as an aggressive tumor with a generally poor prognosis.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Alsupporting
confidence: 78%
“…In addition to RT, lymphedema has been implicated as a potential causative factor in the development of angiosarcoma. 32 Lagrange et al reported that most RIS was high grade, as observed in our study, in which 66% were grade 3. 33 Regarding RIS site, the proportion of sarcomas that arose from the maxillary sinus in the current study cohort (18.9%) was consistent with the data reported by Wang et al 17 RIS traditionally has been viewed as an aggressive tumor with a generally poor prognosis.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Alsupporting
confidence: 78%
“…Reviewed in detail by Monroe and colleagues [68], angiosarcomas of the breast following lumpectomy and radiation therapy for breast cancer are rare but are being reported with increasing infrequency. These secondary angiosarcomas are to be distinguished from primary breast angiosarcomas, which occur in relatively younger women and which have no well-defined risk factors.…”
Section: Angiosarcoma Related To Breast-conservation Therapymentioning
confidence: 99%
“…The result was no evidence of recurrent disease after 18 months, 38 months, and 39 months (Table 5). 33,39 Combining our series of 16 patients (Tables 3 and 4) with 19 patients identified in the literature (Table 5) yielded the following results of reirradiation with or without hyperthermia. Response to treatment was reported for 23 patients.…”
Section: Discussionmentioning
confidence: 97%
“…7,17,31,32 A review of all 92 patients of angiosarcoma after breast-conserving therapy reported in the English literature revealed that 55 of 75 patients (73%) with at least 1 year of follow-up developed a local recurrence after mastectomy (n ¼ 72) or wide local excision (n ¼ 3). 33 In that review, all patients who received adjuvant radiotherapy (n ¼ 1) and/or chemotherapy (n ¼ 3) experienced a local recurrence. Most recurrences (84%) developed within 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation